Reduction of organic nitrates catalysed by xanthine oxidoreductase under anaerobic conditions - Doel, Justin J; Godber, Ben L.J; Eisenthal, Robert; Harrison, Roger (Biochimica et biophysica acta, 2001)
Xanthine oxidoreductase catalyses the anaerobic reduction of glyceryl trinitrate (GTN), isosorbide dinitrate and isosorbide mononitrate to inorganic nitrite using xanthine or NADH as reducing substrates. Reduction rates are much faster with xanthine as reducing substrate than with NADH. In the presence of xanthine, urate is produced in essentially 1:1 stoichiometric ratio with inorganic nitrite, further reduction of which is relatively slow. Organic nitrates were shown to interact with the FAD site of the enzyme. In the course of reduction of GTN, xanthine oxidoreductase was progressively inactivated by conversion to its desulpho form. It is proposed that xanthine oxidoreductase is one of several flavoenzymes that catalyse the conversion of organic nitrate to inorganic nitrite in vivo. Evidence for its further involvement in reduction of the resulting nitrite to nitric oxide is discussed.